SNU: um framework para o desenvolvimento de aplicações voltadas às redes ad-hoc espontâneas - PALMEIRA FILHO, Antonio Sá Fernandes (2007)
Mobile devices have evolved from simple personal digital assistants or cell phones to cutting-edge personal digital assistants, aliasing or combining on-the- y video/audio acquisition and data processing. But giving the best usage to all this new technology in our day-by-day tasks still is challenging. The large variety of devices, the increasing need for ubiquitous mobile services and the network heterogeneity are just some problems developers may nd when deploying for the mobile world. With the popularization of the wireless network technologies, we can nd devices capable of establishing network connections using di erent technologies. Infrastructured networks support good bandwidth with low latency, but they demand an infrastructure of access points that are not available at any place. On the other hand, ad-hoc networks don't need an infrastructure and the communication is done in a peer-to-peer maner. The ad-hoc networks play an important rule in the environments made by mobile devices since they ensure high availability. Spontaneous networks are ad-hoc networks formed occasionally by users that wish to engage in some collaborative task, like a le sharing. In this work we describe a framework to help developers to easily create applications capable of managing and sharing digital content within groups of people in a spontaneous short-range ad-hoc network. We describe the framework architecture, its services and their relationship, as well as some usage scenarios, applications and related works.